Forecasting Dropout Pulmonary TB Control Through the Swot Program and Mapping of at-Risk Areas in Batang District - Irawan, Teguh; Wahyuningsih; Indriono, Anik; Maula, Muhammad Fatih Izzul; Azzahra, Meila (MultiTech Publisher, 2024)
Pulmonary Tuberculosis in Indonesia is still a target for intervention, especially after the Indonesian State launched a TB-free Indonesia program by 2030. This has had a lot of opposition, especially in the treatment process and there are still many TB patients who drop out and even have MDR (Multidrug Resistance TB) status. TB cases in Batang Regency in 2023 increased to 1332 cases, higher than in 2022 which was 1192 cases. This research aims to carry out Forecasting for Controlling drop-out pulmonary TB through the SWOT Program and Mapping of Risk Areas in Batang Regency. This research is a descriptive study with SWOT analysis and Forecasting for Controlling drop-out pulmonary TB, collecting initial data by mapping drop-out TB cases. The research subjects were TB program holders, Head of P2PM, and Technical Implementers at Community Health Centers and Hospitals as well as Triangulation informants, namely Drop Out TB patients. The research results showed that the number of pulmonary TB cases that dropped out in Batang Regency was 111 cases. Drop Pulmonary TB cases were dominant in the age range 51-60 years with 29 cases (26.1%), 72 cases (64.9%) of male gender and 106 drop-out TB sufferers who went to the hospital for treatment. (95.5%). The distribution of Drop Out Pulmonary TB Cases is in the Batang sub-district with 34 cases. Based on the SWOT matrix analysis, it was found that strategies for controlling pulmonary TB dropout in Batang Regency that could be implemented were adding TCM tools, adding network bandwidth to the system, carrying out Information and Education Communication (KIE) to patients, families and the community, ensuring the PMO carried out its duties well